The effect of infrastructures on total factor productivity and its determinants: A study on Mexico - Álvarez Ayuso, Inmaculada C.; Becerril Torres, Osvaldo U.; Del Moral Barrera, Laura E. (Estudios Económicos de El Colegio de México, 2011)
The objective of this research is to identify the effect which infrastructures have on Total Factor Productivity, TFP, and on its components: technical change and efficiency change, of the Mexican states. The methodologies employed are Data Envelopment Analysis to obtain TFP and their components, and panel data econometrics, particularly through the estimation of a model of fixed effects, to determine the effect of the infrastructures. The results show in the first place that technical efficiency is of greater importance to the composition of TFP. Likewise, the existence of a favorable effect of the infrastructures on TFP and its factors is verified.